Design Project Management Application Of The Blind Color Test Android Based - Yudha Dwi Putra Negara; Farihatul Mahbubah (International Journal of Science, Engineering, and Information Technology, 2019)
IT project management is an activity of resources available from IT solution development projects that can produce a system solution that meets predetermined requirements. Developments in the era of technology are moving forward with the development of companies engaged in technology services. This project planning can be prepared using Work Breakdown Structure (WBS), budget plans and network diagrams (AON). The color blind test application system is an application to facilitate the detection of colors early on in someone and also provides accessibility to the black test. By managing a good project management, it is possible to estimate the time and cost needed in implementing the project, so as to minimize the estimated cost due to additional project delays.